World Values Survey, Australia, 2018 - Sheppard, Jill (ADA Dataverse, 2018)
The World Values Survey (WVS) series was designed to enable a crossnational, crosscultural comparison of values and norms on a wide variety of topics and to monitor changes in values and attitudes across the globe. This dataset contains the survey data from the Australian component of the seventh wave of the World Values Surveys carried out in 2018. The World Values Survey is the world’s most comprehensive investigation of political and sociocultural change. It is an international survey with the 2018 ‘wave’ covering at least 95 countries. The purpose of the survey is to investigate worldwide political and sociocultural change and is conducted by a network of social scientists from leading universities around the world. Broad topics covered in the 2018, seventh wave include personal values, trust, gender roles, subjective wellbeing, volunteering, self-perceptions, social and economic environment, inequality, confidence in institutions, politics and democracy, religion, perceptions of older people, perceptions of crime and security, national identity, media and technology. Demographic information includes size of locality, region of residence, occupation of the head of household, and the respondent's age, sex, marital status, number of children, employment status, occupation, social class, country of birth, ethnicity, education, religion, religiosity, political party, and left-right political self-placement.